Weighted sum rate maximization of MISO interference broadcast channels via difference of convex functions programming: A large system analysis - Tabikh, Wassim; Slock, Dirk; Yi Yuan-Wu (2016 IEEE Statistical Signal Processing Workshop (SSP), 2016)
The weighted sum rate (WSR) maximizing linear precoding algorithm is studied in large correlated multiple-input single-output (MISO) interference broadcast channels (IBC). We consider an iterative WSR design via difference of convex functions (DC) programming as in [1], [2] and [3], focusing on the version in [3]. We propose an asymptotic approximation of the signal-to-interference plus noise ratio (SINR) at every iteration.